Characterization of Trametes versicolor laccase-catalyzed degradation of estrogenic pollutants: Substrate limitation and product identification. (February 2018) - Beck, Samuel; Berry, Ellie; Duke, Sarah; Milliken, Alex; Patterson, Hannah; Prewett, Deborah L.; Rae, T. Carter; Sridhar, Varsha; Wendland, Nils; Gregory, Brian W.; Johnson, Corey M.
Abstract: Laccase, the multi-copper oxidase from Trametes versicolor (Tv Lcc), is of interest in wastewater decontamination applications due to its ability to oxidize and remove the estrogenic activity associated with a number of pollutants. In this paper, the known estrogenic pollutants, 17α-ethinylestradiol (EE2), β-estradiol (E2), bisphenol-A (BPA) and bisphenol-S (BPS), were submitted to in vitro incubations with pure Tv Lcc. In the presence of the enzyme, EE2, E2 and BPA all formed a precipitate product, whereas no precipitate was observed in incubations with BPS. Electrospray ionization mass spectrometry identified the precipitate oxidation products as oligomers, consistent with a mechanism involving initial enzymatic production of phenoxy radicals and step-wise oligomer formation via radical coupling. Specifically, BPA, EE2 and E2 products reveal mass spectral evidence of oxyphenylene linkages and oligomer degradation. While the initial rate for BPA oxidation was faster than that for EE2 or E2, no significant rate was observed for BPS incubations. The comparable size and geometry of BPA and BPS indicate that geometric and steric complementarity are not the primary predictors of their reactivity with Tv Lcc. Reactivity differences for such species more likely reside in dissimilarities between their standard redox potentials compared to that for the T1 copper of Tv Lcc. Cyclic voltammetry supports this notion, indicating that BPS oxidation occurs at a potential nearly 300 mV more positive than that for BPA. Together, these data better define which estrogenic pollutants can be oxidized by Tv Lcc in bioremediation applications. Graphical abstract: Highlights: Estrogenic pollutants become high-order oligomeric products in the presence of pure laccase. Kinetic and mass spectral data indicate bisphenol S is not a laccase substrate. Oxidation products for BPA exhibit mass spectral evidence of oxyphenylene linkages. Redox potential is the primary determinant of an acceptable bisphenol substrate for laccase.